Pelatihan Untuk Meningkatkan Market Segmentation Kelompok UMKM di Kota Salatiga - Edwin Zusrony; Budi Santoso, Agustinus; Rakasiwi, Sindhu; Andriana, Myra; Sumarlin, Tantik; Fitrianto, Yuli; Suprapti (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The implementation of community service activities is aimed at the MSME group regarding how to increase market segmentation with various counseling with material on the importance of packaging and labeling, introduction of product sales strategies through e-commerce, introduction of website, digitalization of modern business for MSMEs and the use of Google My Business (GMB). The counseling was carried out by direct interaction between lecturers from the STEKOM University team and participants from the MSME group in the city of Salatiga. Model training and counseling with presentations and hands-on practice using electronic devices, such as laptops, LCDs and smartphones. This outreach program is expected to be sustainable and enable participants to implement strategies to increase market segmentation, especially the MSME group in Salatiga City.